PENANAMAN KARAKTER PEDULI LINGKUNGAN MELALUI KEGIATAN GOTONG ROYONG DI SDN UNYUR - Siti Handayani; Ujang Jamaludin; Suparno Suparno (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The background of this research wasthe importance of theenvironmental care character built from an early agestarting in elementary school, and instilled in various ways; one of which was through mutual cooperation activities. The purpose of this study included two things: first, to determine the implementation of buildingthe environmental care character through mutual cooperation activities at SDN Unyur and second, to determine strategies to fosterthe environmental care character through mutual cooperation activities at SDN Unyur. This research was descriptive qualitative research. This research was conducted at SDN Unyur, Serang, Banten. The results showed that the implementation of building environmental care character through mutual cooperation at SDN Unyur included environmental care activities in the classroom, environmental care activities outside the classroom, and annual environmental care activities. The strategy for fostering theenvironmental care character through mutual cooperation activities at SDN Unyur was instilled by making teachers as role models, giving sanctions and appreciation to students, and providing facilities and infrastructure supporting the manifestation of the environment care character.The background of this research wasthe importance of theenvironmental care character built from an early agestarting in elementary school, and instilled in various ways; one of which was through mutual cooperation activities. The purpose of this study included two things: first, to determine the implementation of buildingthe environmental care character through mutual cooperation activities at SDN Unyur and second, to determine strategies to fosterthe environmental care character through mutual cooperation activities at SDN Unyur. This research was descriptive qualitative research. This research was conducted at SDN Unyur, Serang, Banten. The results showed that the implementation of building environmental care character through mutual cooperation at SDN Unyur included environmental care activities in the classroom, environmental care activities outside the classroom, and annual environmental care activities. The strategy for fostering theenvironmental care character through mutual cooperation activities at SDN Unyur was instilled by making teachers as role models, giving sanctions and appreciation to students, and providing facilities and infrastructure supporting the manifestation of the environment care character.